The Development of Learning Management Activities by Applying Problem-Based Learning Management to Develop Analytical Thinking in Science and Technology Subjects for Grade 9 Students - Duangrat Thawatchoti; Wisarut Payoungkiattikun; Tipubon Tippalert (Gagasan Pendidikan Indonesia, 2023)
This research aimed to; (1) Develop learning management activities by applying problem-based learning for grade 9 students in science and technology subjects, meeting the 70/70 criteria. (2) Develop analytical thinking among grade 9 students to meet the 70 percent threshold. Moreover, (3) study satisfaction with learning management by applying problem-based learning. The researchers developed learning management activities for grade 9 students in science and technology courses in this research by applying problem-based learning. The tools used in the research include; (1) Learning Management Plan 5 Plans. (2) analytical thinking Tests. Moreover, (3) satisfaction questionnaires. Statistics used to analyze the data include percent average and standard deviations. The sample groups used in the research are grade 9 students and 23 students from a school in Kalasin province, Indonesia. They were collected by; (1) Analytical thinking Test 30 items. (2) Satisfaction assessment 10 items. The research results showed; (1) The development of learning management activities by applying problem-based learning for students in grade 9 in science and technology subjects to be effective 72.12/70.76, higher than the specified threshold of 70/70. (2) The development of analytical thinking accounted for 71.51%. Meet the 70 % threshold. It shows that managing learning by applying problem-based learning can develop analytical thinking. Moreover, (3) Students are satisfied with learning management by applying problem-based learning. It averaged 4.74, with the highest level of satisfaction.